Focusing on Organizational Change - Judge, William Q. (Open textbook library., 2012)
Never before have strategic leaders been confronted with so much overwhelming change. The traditional approach is to teach the leader or leaders how to direct or control the organizations' reaction on a monthly, weekly, or even daily basis. This approach is stressful and overwhelming for executive leaders, makes middle managers feel torn between honoring their senior leaders and listening to the demands of front line employees, and is alienating for front line employees. Focusing on Organizational Change offers an alternative to the traditional approach by focusing on building the change capacity of the entire organization in anticipation of future pressures to change. Based on systematic research of more than 5,000 respondents working within more than 200 organization or organizational units conducted during the previous decade, this book offers a clear and proven method for diagnosing your organizational change capacity. While building organizational change capacity is not fast or easy, it is essential for effective leadership and organizational survival in the 21st century.